S=1+2+2 mũ 2+2 mũ 3=2 mũ 4 +.....+2 mũ 2013 tính tổng S
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Rightarrow2S=2+2^2+2^3+...+2^{101}\)
\(\Rightarrow2S-S=2+2^2+2^3+...+2^{101}-1-2-2^2-...-2^{100}\)
\(\Rightarrow S=2^{101}-1\)
\(2S=2+2^2+...+2^{11}\)
\(2S-S=S=\left(2+2^2+....+2^{11}\right)-\left(1+2+.....+2^{10}\right)\)
\(S=2^{11}-1\)
S= 2 + 22 + 23 + 24 + ... + 2100
S x 2 = (2+22+23+24+...+2100)x2
S x 2 = 22+23+24+25+...+2101
S x 2 - S = 22+23+24+25+...+2101 - 2 - 22 - 23 - 24 - ... - 2100
S = 2101 - 2
S = (TỰ TÍNH NHÉ MK LƯỜI LẮM)
\(S=1+2^2+2^4+2^6+2^8+...+2^{2024}\\2^2\cdot S=2^2\cdot(1+2^2+2^4+2^6+2^8+...+2^{2024})\\4S=2^2+2^4+2^6+2^8+2^{10}+...+2^{2026}\\4S-S=(2^2+2^4+2^6+2^8+2^{10}+...+2^{2026})-(1+2^2+2^4+2^6+2^8+...+2^{2024})\\3S=2^{2026}-1\\\Rightarrow S=\dfrac{2^{2026}-1}{3}\\Toru\)
\(S=1+2^1+...+2^{100}\)
\(\Rightarrow2S=2+2^2+...+2^{101}\)
\(\Rightarrow2S-S=2+2^2+...+2^{101}-1-2^1-...-2^{100}\)
\(\Rightarrow S=2^{101}-1\)